Clinical outcome of Crohn's disease treated with infliximab - (:unkn) unknown (H G E UPDATE MEDICAL PUBLISHING S A, 2003)
Background/Aims: Controlled studies in humans have shown the role of antibodies to tumor necrosis factor-alpha in the treatment of both fistulizing and inflammatory Crohn's disease. The aim of this study is to report the results of a multicenter clinical trial to evaluate efficacy of infliximab in Crohn's disease patients who are refractory to conservative drugs or fistulizing Crohn's disease. Methodology: This trial was carried out at 5 university and community hospitals, in Turkey. A total of 25 patients with Crohn's disease that were unresponsive to conventional medical therapy, participated; 17 of the 25 were in the fistulizing disease group and,8 were in the inflammatory disease group. Clinical response was classified according to fistula drainage, diarrhea as positive response or no response. Results: Overall response rate was 92% (23/25), regardless of the disease group, after first infusion of infliximab. Sixteen out of 17 patients in the fistulizing disease group had a positive response. Fourteen of the 16 positive responders later relapsed. Median duration of response was 8 weeks (range, 2-35 wk). Active inflammatory disease patients had a positive response rate of 75% (6/8) and two of the patients were nonresponders. A further two patients relapsed at week 14. Two patients in both arms of the study were still in remission at the end of the study. Major adverse events were: pneumonia in one patient, skin infections in two patients, pulmonary thromboembolism. and death in one patient. Conclusions: Infliximab treatment seems to be more effective in Crohn's disease patients especially in those with fistulizing disease than those with non-fistulizing, inflammatory disease. It is evident that maintenance of remission might be achieved with ongoing maintenance therapy. We suggest maintenance of infliximab therapy.
Keywords: Crohn's disease (CD); treatment (Therapy); tumor necrosis factor-alpha (TNF-alpha); TNF-ALPHA; ARTICLE; FISTULAS; EFFICACY; SAFETY